Malawi: Farmwise - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Bessie Nyirenda describes how a database system, an online input calculator, and email are helping women farmers in Malawi to improve agricultural production.